Impact of childhood trauma on sensorimotor gating in Chinese patients with chronic schizophrenia. (May 2018) - Li, Xianbin; Tian, Qing; Bo, Qijing; Zhang, Guangping; Zheng, Wei; Wen, Yujie; Tang, Yilang; Wang, Chuanyue
Abstract: We investigated the relationship between childhood trauma (CT) and sensorimotor gating in Chinese patients diagnosed with chronic schizophrenia. Seventy-five patients were assessed with the Childhood Trauma Questionnaire-Short Form (CTQ-SF), and then the modified paradigm, perceived spatial separation-induced prepulse inhibition (PSS PPI) and the perceived spatial co-location PPI (PSC PPI or classical PPI) were applied to test sensorimotor gating. Startling stimuli (90 dB) were presented either alone or preceded by discrete prepulse stimuli of 4 dB in a background 60-dB noise level. Associations between CT and various PPI paradigms were statistically analyzed. Univariate analysis revealed the absence of a significant correlation between CT and PPI paradigms ( p > 0.05). However, multiple linear regression analyses revealed that sexual abuse and the positive and negative syndrome scale (PANSS) score were negatively correlated with PSS PPI ( p = 0.029 and 0.008, respectively). On the other hand, female sex and history of smoking were positively correlated with PSS PPI ( p = 0.044 and 0.043, respectively). In conclusion, the results of this study suggest that CT can be a predisposing factor that affects sensorimotor gating in schizophrenia patients. Highlights: This was among the first studies to examine childhood trauma on sensory gating in patients with schizophrenia. We used the modified paradigm, perceived spatial separation-induced PPI (PSS PPI) to test the sensory gating. Our results suggest that childhood trauma can be a predisposing factor that affects sensory gating in schizophrenia patients.